“The role of online disinformation in supporting SLAPP lawsuits in South Africa: A case study of Zunaid Moti’s online campaign and SLAPP lawsuit against amaBhungane and the impact on its journalists” - Roodt, Daniel (Stellenbosch : Stellenbosch University, 2025)
Thesis (MA)--Stellenbosch University, 2025.